2016
DOI: 10.7314/apjcp.2016.17.s1.65
|View full text |Cite
|
Sign up to set email alerts
|

Students' Knowledge and Attitudes Towards Smoke-Free Universities: Changes Since Enactment of Vietnamese Tobacco Control Legislation

Abstract: Background: In 2013, legislation in Vietnam regulated smoking in public areas. Included was a ban on indoor smoking at universities. Objective: Since awareness and attitude are moderators of the effectiveness of smokefree policy, ou aim was to assess changes in students' knowledge and attitude tosecond hand smoke (SHS) and awareness and support of smoke-free legislation at four Vietnamese universities, one year after legislative changes. Methods: A two-phase cross sectional study of undergraduate students usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…We included 105 references, published between 1993 and 2019, representing 75 unique studies, which described the development or implementation and evaluation of SF/TF university policies in various universities. As shown in Figure 2, most studies were conducted in North America (50/75, 66.7%), including the United States (46 studies), and Canada (4 studies: [9,[28][29][30][31]); one study was conducted in Brazil [32]; 10 studies (14.7%) were conducted in Asian countries, such as Japan (3 studies: [33][34][35]), China [36], South Korea [37], Taiwan [38], Vietnam [39], India [40], Pakistan [41], and Malaysia [42]; 4 studies came from Europe (Germany [43], Ireland [44][45][46], Switzerland [47], and Russia [48]); 6 from the Middle East and North Africa (Bahrain [49], Egypt [50], Israel [51], Lebanon [52], Saudi Arabia [53], and Sudan [54]; and 4 from Oceania (3 studies from Australia [55][56][57][58], 1 from New Zealand [59]). While the majority of the studies were of single universities, some reported case studies or analyses of multiple universities based in Australia [55], Canada [28], China [36], India [40], New Zealand [59], Russia…”
Section: Charting Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 105 references, published between 1993 and 2019, representing 75 unique studies, which described the development or implementation and evaluation of SF/TF university policies in various universities. As shown in Figure 2, most studies were conducted in North America (50/75, 66.7%), including the United States (46 studies), and Canada (4 studies: [9,[28][29][30][31]); one study was conducted in Brazil [32]; 10 studies (14.7%) were conducted in Asian countries, such as Japan (3 studies: [33][34][35]), China [36], South Korea [37], Taiwan [38], Vietnam [39], India [40], Pakistan [41], and Malaysia [42]; 4 studies came from Europe (Germany [43], Ireland [44][45][46], Switzerland [47], and Russia [48]); 6 from the Middle East and North Africa (Bahrain [49], Egypt [50], Israel [51], Lebanon [52], Saudi Arabia [53], and Sudan [54]; and 4 from Oceania (3 studies from Australia [55][56][57][58], 1 from New Zealand [59]). While the majority of the studies were of single universities, some reported case studies or analyses of multiple universities based in Australia [55], Canada [28], China [36], India [40], New Zealand [59], Russia…”
Section: Charting Resultsmentioning
confidence: 99%
“…Impact only studies were predominantly quantitative (30/35, 85.7%), mostly based on cross-sectional surveys collecting information about various indicators of impact (further described below). Some impact studies included empirical research used to test interventions aimed at improving the acceptance or use of a policy, such as before-after studies [33,39,47,62,[75][76][77][78][79], or quasi-experimental interventions [37,48].…”
Section: Type Of Research Design and Research Objectivesmentioning
confidence: 99%